Durian (Durio zibethinus L.): Nutritional Composition, Pharmacological Implications, Value-Added Products, and Omics-Based Investigations - Gholamreza Khaksar; Sudarat Kasemcholathan; Supaart Sirikantaramas (Horticulturae, 2024)
Durian (Durio zibethinus L.), a tropical fruit celebrated in Southeast Asia for its distinct flavor, is the focus of this comprehensive review. The fruit’s pulp is rich in high-value bioactive compounds, including gamma-glutamylcysteine, a precursor to the essential antioxidant glutathione. With durian cultivation gaining prominence in Southeast Asia due to its economic potential through cultivar enhancement, an in-depth examination of durian-related research becomes crucial. This review explores the health benefits of durian, analyzing the nutritional compositions and bioactive compounds present in the pulp, peel, and seed. It also underscores durian-based food products and the potential for valorizing durian waste. This review encapsulates the significant advancements made in omics-based research, aimed at deciphering the molecular complexities of durian fruit post-harvest ripening and the metabolic shifts impacting its sensory attributes. It is the first to summarize studies across genome, transcriptome, and metabolome levels. Future research should prioritize the development of molecular markers to accelerate the breeding of elite cultivars with preferred traits. It also proposes the exploration of durian waste valorization, including underexplored parts like flowers and leaves for their bioactive compounds, to promote a sustainable bioeconomy. Finally, it suggests the development of innovative durian products catering to the tastes of health-conscious consumers.